Outcome of emergency surgery for severe neuroleptic‐induced colitis: results of a prospective cohort. (December 2016) - Abdalla, S.; Brouquet, A.; Lazure, T.; Costaglioli, B.; Penna, C.; Benoist, S.
Abstract: Aim: The study evaluated the outcome of severe acute antipsychotic (neuroleptic) drug related colitis requiring emergency surgery. Method: From 2009 to 2014, 20 patients underwent emergency surgery for acute and severe neuroleptic‐related ischaemic colitis. Neuroleptic‐induced colitis was defined as another cause besides inflammatory, infectious or ischaemic colitis with a relationship to treatment by antipsychotic drugs. Results: The main drugs involved were cyamemazine ( n = 9, 45%), loxapine ( n = 5, 25%), haloperidol ( n = 4, 20%) and alimemazine ( n = 4, 20%). Most ( n = 14, 70%) patients presented with haemodynamic instability requiring massive resuscitation and vasopressive drugs. CT signs of digestive impairment were found in 13 (65%) patients having emergency surgery. The lesions were pancolonic in 40%; transparietal necrosis was found in 45% and 15% had colonic perforation. Twelve (60%) patients had total or subtotal colectomy and eight (40%) a segmental colectomy with colostomy or ileostomy in all cases. The postoperative mortality was 15% and morbidity was 70%, necessitating surgical reintervention in two (10%) patients. Of the 17 surviving patients, 11 (64.7%) had restoration of intestinal continuity after a median delay of 103 days, with a postoperative morbidity rate of 36.3%. In the intent‐to‐treat population, the permanent stoma rate was 30%. Conclusion: The morbidity and mortality of surgery for neuroleptic‐drug‐induced colitis is higher than for colitis due to other causes. A better knowledge of this condition should lead to early diagnosis.